On Coupled Delayed Van der Pol-Duffing Oscillators - Pandey, Ankan; Mitra, Mainak; Ghose-Choudhury, A; Guha, Partha (Journal of Applied Nonlinear Dynamics, 2026)
We investigate the dynamics of a delay differential coupled Duffing-Van der Pol oscillator equation. Using the Lindstedt's method, we derive the in-phase mode solutions and then obtain the slow flow equations governing the stability of the in-phase mode by employing the two variable perturbation method. We solve the slow flow equations using series expansion and obtain conditions for Hopf bifurcation and studied stability of the in-phase mode. Finally, we studied stability and bifurcations of the origin. Our interest in this system is due to the fact that it is related to the coupled laser oscillators.